Model Green Scor Untuk Pengukuran Kinerja Green Supply Chain Management (GSCM) Industri Kelapa Sawit di Indonesia - Rangga Primadasa; Akh Sokhibi (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2020)
This paper aims to create Key Performance Indicators (KPIs) to evaluate green supply chain management (GSCM) for palm oil industry in Indonesia. Green supply chain management (GSCM) is a method to integrate environmental aspects to their supply chain. The method in creating KPIs using Green SCOR Model as a basis to develop green objectives and all of indicators. There are 23 KPIs from 9 green objectives for GSCM of palm oil industry in Indonesia. To ensure KPIs more precise then the impotance level of KPIs are measured using analaytic hierarchy process (AHP). According to the experts in palm oil industries there is managing plantations and palm oil mill using ISPO and RSPO certification as the dominant green objectives (29.7 %), followed by minimize and tackle emission from global warming gass (15,9 %), and manage waste ( 11,8 %).